Pelaksanaan Resheduling pada Pembiayaan Modal Kerja Bermasalah dengan Akad Murabahah - Annisa Putri Anugrah (Journal on Education, 2023)
Rescheduling implementation is to find out how much income Islamic financial institutions earn through rescheduling (Rescheduling) for customers who fail to fulfill their obligations. By resecheduling, Islamic financial institutions can minimize losses that occur as a result of channeling the funds provided. The mechanism for implementing rescheduling for troubled working capital financing uses a murabahah contract at BPRS X, in accordance with Islamic economics and the DSN MUI Fatwa. The rescheduling mechanism at BPRS ARTHA MADANIis carried out by providing an extension of the financing period, the remaining principal to the customer is used as new financing in accordance with the installment value of the customer's ability to pay, the rescheduling process at BPRS ARTHA MADANIis carried out by changing the financing period, payment schedule and installment amount, but does not change the remaining balance payment at the beginning of the contract. The rescheduling implementation at BPRS ARTHA MADANIwent well, the rescheduling proved to be more effective in resolving problematic financing, the rescheduling implementation at BPRS ARTHA MADANIwas also in accordance with the basic principles of Islamic economics, letter Al-Baqarah article 280 and DSN legal letters Article 280. 48/DSN-MUI/II/2005 regarding the rearrangement of the murabaha law.